Examining the Financial Literacy of Healthcare Professionals: A Research on a Provincial Health Directorate - Mustafa Özyeşil; Havane Tembelo; Haydar Sur (AVES, 2024)
Aim: This research aimed to assess the financial literacy levels of healthcare professionals working at a Provincial Health Directorate and examine their relationships with various financial domains. Methods: The study utilized a cross-sectional online survey. The financial literacy scale was employed to assess the financial knowledge and compentencies of healthcare professionals, providing a structured evaluation of their understandig across various financial domains. Statistical analyses, including correlation analysis, independent samples t-test, and one-way ANOVA, were performed using SPSS-25 and R programs. Results: A total of 240 participants took part, comprising 52.1% males and 47.9% females, aged between 20 and 65 years. Younger healthcare professionals (p=.017) and males (p=.001) demonstrated higher financial literacy levels. Significant correlations were found between financial literacy and domains such as investment instruments, debt and risk management, and personal finance management. Weak but positive relationships were observed between financial literacy and digital assets, indicating emerging trends in digital finance awareness. For instance, males exhibited higher proficiency in investment instruments and debt management, while younger professionals displayed higher knowledge in investment areas. Conclusion: The findings underscore the importance of targeted financial education for healthcare professionals, highlighting the need for sector-specific training programs. Enhanced financial literacy is essential for improving financial decision-making, ultimately benefiting both personal financial well-being and professional performance in the healthcare sector.